2D Dubins Path in Environments with Obstacle. (11th November 2013) - Yang, Dongxiao; Li, Didong; Sun, Huafei
Abstract : We recapitulate the achievement about the Dubins path as well as some precise proofs which are important but omitted by Dubins. Then we prove that the shortest path (R * -geodesic) in environments with an obstacle consists of no more than five segments, each of which is either an arc or a straight line. To obtain such R * -geodesic, an effective algorithm is presented followed by a numerical simulation as verification.